The iterative complex demodulation applied on short and long Schumann resonance measured sequences - ONDRÁŠKOVÁ, Adriena; ŠEVČÍK, Sebastián (Contributions to Geophysics and Geodesy, 2014)
The precise determination of instantaneous frequency of Schumann resonance (SR) modes, with the possibility of application to relatively short signal sequences, seems to be important for detailed analysis of SR modal frequency variations. Contrary to commonly used method of obtaining modal frequencies by the Lorentz function fitting of DFT spectra, we employ the complex demodulation (CD) method in iterated form. Results of iterated CD method applied on short and long measured sequences are compared. Results for SR signals as well as the comparison with Lorentz function fitting are presented. Decrease of frequencies of all first four SR modes from the solar cycle maximum to solar cycle minimum has been found using also the CD method.